Crafting authenticity: An ethnography of conservation practice. (March 2013) - Jones, Siân; Yarrow, Thomas
This article explores how authenticity is produced through different forms of expertise and skill, as they are negotiated and aligned in the daily practices of conservation. Focusing on the traditional craft practices of stonemasons, the authors trace their relations to the broader nexus of experts responsible for conserving Glasgow Cathedral. They show that authenticity is a distributed property of distinct forms of expert practice as they intersect with one another and, crucially, with the material conditions of specific heritage sites. It is argued that, in the context of conservation practice, authenticity is neither a subjective, discursive construction nor a latent property of historic monuments waiting to be preserved. Rather it is a property that emerges through specific interactions between people and things.